2012
DOI: 10.3109/09593985.2012.734011
|View full text |Cite
|
Sign up to set email alerts
|

Stress among healthcare students – A cross disciplinary perspective

Abstract: Students from PT, CD, and NS programs perceived similar levels of stress. The academic factor was perceived as the most important source of stress by students from the three departments, despite differences in the academic educational programs. Further studies are needed to generalize these results and enable a comparison between healthcare students and other students' stress perceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 19 publications
1
38
0
3
Order By: Relevance
“…The stressors as well as the coping strategies, utilised by health care students, have also been well documented in recent years (Jacob, Itzchak & Raz 2013;Sabih, Siddiqui & Baber 2013;Sani et al 2012;Walsh et al 2010). Levels of stress in health care students have been reported to be so high that it could even be linked to psychological morbidity.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%
“…The stressors as well as the coping strategies, utilised by health care students, have also been well documented in recent years (Jacob, Itzchak & Raz 2013;Sabih, Siddiqui & Baber 2013;Sani et al 2012;Walsh et al 2010). Levels of stress in health care students have been reported to be so high that it could even be linked to psychological morbidity.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%
“…As these students will become future health care providers, it is important for institutions to teach them how to cope with stress themselves, as well how to treat stress in their future patients. 1 Medical, nursing, dental, pharmacy, occupational therapy, and physical therapy students have reported high levels of perceived stress. [1][2][3]10 Student stress often stems from academic load, classroom environment, faculty interaction, illness, and emotional concerns outside of the classroom or clinic.…”
Section: Introductionmentioning
confidence: 99%
“…1 Medical, nursing, dental, pharmacy, occupational therapy, and physical therapy students have reported high levels of perceived stress. [1][2][3]10 Student stress often stems from academic load, classroom environment, faculty interaction, illness, and emotional concerns outside of the classroom or clinic. Until recently, the literature on stress experienced by students in complementary and alternative medicine (CAM) has been scarce, but a recent study among chiropractic students indicated that students in their 4th year of doctoral study reported the highest levels of stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El factor académico fue percibido como la fuente más importante de estrés de los estudiantes de los tres departamentos, a pesar de las diferencias en los programas de educación académica. Estos autores sugieren que se necesitan más estudios para generalizar estos resultados y permitir la comparación entre los estudiantes de la salud y las percepciones de estrés de otros estudiantes [14].…”
Section: Discusion Y Conclusiónunclassified